BERRY WONDER-CROPS IN THE FARMER SECTOR: MARKETING SPECULATION OR VALUABLE VITAMIN SUPPLEMENT TO THE DIET - Rozhko, І.С.; Rozhko, І.М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The article emphasizes the fact that cultivation of non-traditional berry crops (such as blackberries, honeysuckle, and others) should not only be economically beneficial but also environmentally safe in terms of both safety of the berries themselves and their impact on the environment. When choosing crops, farmers should think critically basing on principal knowledge of the courses of school biology and geography, as well as reliable professional information, rather than blindly follow the mass advertising attack of the information and communication resources. It is necessary to consider the ecological risks and threats that may arise during their cultivation. Considering that blackberries and edible honeysuckle require a lot of water for irrigation, and given the geographic conditions of the Main European Watershed in western Ukraine, water scarcity will increase due to global climate change trends, the authors of the research believe that the increasing cost of cultivating these berry crops will only cause economic losses. It will have a negative eco-economic effect, which will take decades to overcome, provided that appropriate reclamation work is carried out. Cultivation of invasive raspberries can be unpredictable since the plant is highly competitive. Without proper care, there is a risk of uncontrolled spread, which poses a threat to natural ecosystems. Taking into account the present problems associated with introduced species of agricultural crops or quazi decorative plants and pollinators, such as Sosnowsky's hogweed (Heracleum sosnowskyi Manden.), Canadian goldenrod (Solidago canadensis L.), farmers should be extremely cautious in making decisions.